Epistemological obstacle on the topic of prism: A phenomenological study - Cahdriyana, Rima Aksen; Sintawati, Mukti (Journal of Honai Math, 2024)
Mathematics learning is often hindered by epistemological obstacles that affect students’ conceptual understanding. In geometry, students frequently struggle to identify and analyze fundamental properties of prisms, despite instructional efforts to improve comprehension. Prior research has primarily focused on procedural fluency rather than the cognitive barriers students face in interpreting mathematical definitions. Addressing this gap, this study investigates the epistemological obstacles eighth-grade students encounter in understanding prisms. Specifically, it examines students’ ability to determine whether a geometric figure qualifies as a prism based on definitional characteristics and to analyze the relationship between two figures with equal volumes. This qualitative study employs a phenomenological approach, involving six purposively selected eighth-grade students. Data were collected through written tests and semi-structured interviews, then analyzed in three stages: identifying core ideas from student responses, categorizing these ideas into conceptual groupings, and thematizing the categorized data into key discussion themes. Findings reveal that students struggle to identify prisms due to difficulties recognizing defining characteristics and determining bases, resulting from didactic transposition issues such as oversimplified definitions, misinterpretation of concepts, and curricular limitations. At the C4 level of Bloom’s Taxonomy, students also struggle to analyze mathematical statements due to reliance on teacher-provided examples. This study contributes to mathematics education by highlighting cognitive barriers in geometric reasoning. The findings emphasize the need for instructional strategies that enhance conceptual clarity and adaptive problem-solving, ultimately fostering deeper geometric understanding.